1993
DOI: 10.1002/ddr.430280320
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, endothelium, and purines

Abstract: This article focuses on the events involving purine nucleotides and nucleosides during the initial responses of the cerebral vascular bed to ischaemia. In particular, the role of ATP released from endothelial cells which acts on P,,-purinoceptors, leading to production of nitric oxide and subsequent vasodilatation, will b e considered. A relation between these events and the involvement of purines in the longer term degenerative consequences of ischaemia seems unlikely.o 1993 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Also, adenosine was not collected in the effluent until long after the hyperemic response occurred, because ADP, after breakdown of released ATP, acts as an inhibitor of 59-nucleotidase breakdown of AMP to adenosine (Ishibashi et al, 1985). Years later, after the seminal studies of Robert Furchgott and others showed that ATP acted on endothelial P2 receptors to release NO, resulting in vasodilation, and it was shown that ATP was released from endothelial cells by hypoxia and increased flow (Bodin et al, 1991;Vials and Burnstock, 1996), Burnstock (1993b) proposed that reactive hyperemia was due to ATP release from endothelial cells during hypoxia acting to release NO. This took place rapidly, and only later, after ATP was broken down by ectoenzymes to adenosine, did coronary vasodilation of vascular smooth muscle via P1 receptors contribute to the hyperemic response.…”
Section: E Coronary Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, adenosine was not collected in the effluent until long after the hyperemic response occurred, because ADP, after breakdown of released ATP, acts as an inhibitor of 59-nucleotidase breakdown of AMP to adenosine (Ishibashi et al, 1985). Years later, after the seminal studies of Robert Furchgott and others showed that ATP acted on endothelial P2 receptors to release NO, resulting in vasodilation, and it was shown that ATP was released from endothelial cells by hypoxia and increased flow (Bodin et al, 1991;Vials and Burnstock, 1996), Burnstock (1993b) proposed that reactive hyperemia was due to ATP release from endothelial cells during hypoxia acting to release NO. This took place rapidly, and only later, after ATP was broken down by ectoenzymes to adenosine, did coronary vasodilation of vascular smooth muscle via P1 receptors contribute to the hyperemic response.…”
Section: E Coronary Vesselsmentioning
confidence: 99%
“…It was also noted that although reactive hyperemia occurred after about 10 seconds, adenosine did not appear in the perfusate until about 90 seconds. In a counterhypothesis, Burnstock (1993b) proposed that the initial phase of vasodilation after hypoxia was due to ATP released from endothelial cells to cause vasodilation via NO, whereas adenosine (after breakdown of ATP) contributed only to the later stages of reactive hyperemia by acting on P1 receptors on the smooth muscle. The delay in appearance of adenosine in the perfusate was explained by the fact that ADP (after rapid breakdown of ATP) inhibits 59-nucleotidase, the enzyme that mediates breakdown of AMP to adenosine.…”
Section: Ischemiamentioning
confidence: 99%
“…137 Ischemia and hypoxia lead to a substantial release of ATP from endothelial cells, 64 and adenosine is released from hypoxic heart and skeletal muscle. 138 Adenosine has several cardiovascular protective effects in addition to vasodilation, including the promotion of endothelial cell proliferation and an increased expression of VEGF mRNA. 139 Adenosine also appears to play an important role in preconditioning.…”
Section: Implications For Vascular Diseasementioning
confidence: 99%
“…Although reactive hyperemia occurs ≈10 seconds after resumption of blood flow, adenosine does not appear in the perfusate until ≈90 seconds later because ADP, the first breakdown product, inhibits ecto-5′nucleotidase (CD73). Burnstock 22 claimed that ATP, released during hypoxia from endothelial cells promoting the production of nitric oxide (NO), is the compound initially responsible for reactive hyperemia and that adenosine, after breakdown of ATP, acts later as a dilator via A 1 receptors on smooth muscle.…”
mentioning
confidence: 99%